2020
DOI: 10.1136/gutjnl-2019-320230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new enterosynes using prebiotics: roles of bioactive lipids and mu-opioid receptor signalling in humans and mice

Abstract: ObjectiveThe enteric nervous system (ENS) plays a key role in controlling the gut-brain axis under normal and pathological conditions, such as type 2 diabetes. The discovery of intestinal actors, such as enterosynes, able to modulate the ENS-induced duodenal contraction is considered an innovative approach. Among all the intestinal factors, the understanding of the role of gut microbes in controlling glycaemia is still developed. We studied whether the modulation of gut microbiota by prebiotics could permit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Among the potential candidate-mediators, we can mention butyrate, which is produced by D. welbionis J115 T from myo-inositol and known to increase BAT thermogenesis, 38 but also other specific bioactive lipids controlling glucose metabolism and inflammation. 39 40 However, we did not find any increase in the levels of butyrate in the plasma or in the caecal content (online supplemental figure 6).…”
Section: Gut Microbiotamentioning
confidence: 58%
“…Among the potential candidate-mediators, we can mention butyrate, which is produced by D. welbionis J115 T from myo-inositol and known to increase BAT thermogenesis, 38 but also other specific bioactive lipids controlling glucose metabolism and inflammation. 39 40 However, we did not find any increase in the levels of butyrate in the plasma or in the caecal content (online supplemental figure 6).…”
Section: Gut Microbiotamentioning
confidence: 58%
“…Since 12(S)-HETE is considered as a second messenger that transmits signals from activated MOR, further experiments examined whether MOR is a receptor controlling intestinal contractions and glucose metabolism. The results showed that MOR agonist DAMGO significantly decreased frequency and contraction amplitude of the duodenum of diabetic mice; moreover, this effect was dependent on PPARγ [20].…”
Section: Discussionmentioning
confidence: 93%
“…Finally, Hasegawa et al [16] suggested that both unsaturated fatty acids and phospholipids can enhance binding of a purified MOR. Additionally, recent studies established that bioactive lipids and MOR cooperate in diabetes [20]. Namely, chronic oral administration of the lipid, 12(S)-hydroxyeicosatetraenoic [12(S)-HETE] reduced duodenal contractions and improved glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…After a 10 h of fasting, an OGTT (3 g of glucose/kg of body weight) was performed in mice at day 7. Glycaemia was recorded from −30 to 120 min, and insulin and glucagon levels were measured and analyzed at −30, and +15 min as previously described [ 13 ].…”
Section: Methodsmentioning
confidence: 99%